Exploring postnatal and newborn home care experiences of rural and remote mothers in Pakistan whose neonates were admitted to the hospital: A qualitative study - Mika Kuriyama; Moe Nakazora; Md Moshiur Rahman; Mari Sato; Saima Gillani; Sadia Habib; Yoko Shimpuku (PLoS ONE, 2026)
Background The neonatal mortality rate in Pakistan has been the second highest worldwide. Since mortality rate is higher in rural area than in urban area, to understand newborn care and response to progressing disease by rural families is vital to comprehend the background of poor neonatal outcomes. But in Pakistan research on newborn home care is scarce. This study aimed to understand the local context of neonatal morbidity derived from rural and remote Pakistan by exploring the postnatal and newborn home care experiences of mothers whose neonates required admission after being cared for at home. Methods This qualitative descriptive study conducted in-depth, individual, semi-structured interviews with 15 mothers and three family members with children admitted to the neonatal unit of a tertiary hospital from home. Seven pediatric and obstetric staff were also interviewed for data triangulation. Thematic analysis was used to extract themes and sub-themes, and to develop a thematic map. Results Lack of early initiation and exclusive breastfeeding, administration of prelacteals, and suboptimal bathing, wiping, wrapping, and umbilical cord care were identified; they were influenced by family experiences. Short postnatal stays, and lack of postnatal care and health education from facilities, left mothers with traditional care only. Very low birth weight neonates had been cared for at home. From the analysis, five themes were identified. They were gender roles, health literacy, health seeking behavior, lack of preventive care, and a high burden of low birth weight. Conclusion This study identified local newborn home care influenced by familial traditional norms that could make neonates susceptible to infection, dehydration, malnutrition, and hypothermia. Multiple healing approaches and health service quality may have affected families’ ability to seek timely medical attention. Strengthening facility preventive care, and families’ health literacy through culture-sensitive health education, is essential in antenatal and postnatal care, and during admission. Appropriate timing of home discharge, with newborn care counselling, is also vital, considering the high burden of preterm births and low birth weight.